Pengaruh kondisi keuangan, fasilitas perusahaan, dan iklim organisasi terhadap kepatuhan pajak badan (survei pada wajib pajak badan yang terdaftar di KPP Pratama Tampan Kota Pekanbaru) - Dwidya Senni Aprilia; Zirman '; Yessi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to examine and obtain empirical evidence on tax compliance on corporate taxpayers registered in KPP Pratama Tampan, Pekanbaru. Variables to be tested in this study is the financial condition, corporate facilities, and organizational climate (as independent variables) on tax compliance on the Taxpayer (the dependent variable)The data in this study is primary data obtained from questionnaires distributed directly to the respondents. Respondents in this study is a tax professional who works at a company registered in KPP Pratama Tampan who have served a minimum of 1 year and never filled out tax returns. Data collected from 92 respondents. In this study, the data obtained will be processed by multiple linear regression models (multiple regression) that use partial hypothesis test (t-test)The results show that the financial condition, corporate facilities, andsignificant organizational climate has a positive effect partially on corporate tax compliance on corporate taxpayers registered in KPP Pratama Tampan, Pekanbaru. Based on the calculation of the value of coefficient of determination (R2) obtained a value of 0.577. This suggests that the financial condition, corporate facilities, and organizational climate influence for 57.70% of the Tax Compliance Board and the remaining 43.30% is influenced by other variables.Keywords: Financial Condition, Corporate Facilities, Organizational Climate and Tax Compliance Board.